Interdisciplinary participation in climate-adapted urban land-use planning – findings of two gaming simulations in the city of Bottrop, Germany - Marisa Fuchs; Madeleine Loren Kirstein (International Journal of Climate Change Strategies and Management)
Purpose – Sustainable and climate-adapted urban development requires integrative governance approaches and forms of collaboration between different disciplinary actors in urban society. Integrative approaches are a particular challenge for those planning cultures in which they are not yet sufficiently established. This also applies to formal urban land-use planning in Germany, which forms the governance setting of this study. This study aims to examine how interdisciplinary participation in formal urban land-use planning contributes to the consideration of climate adaptation in the planning process. Design/methodology/approach – This paper traces the process of two differently designed interdisciplinary participation formats based on the methodological framework of a gaming simulation, each in the context of a formal urban land-use planning procedure in Bottrop, Germany. The gaming simulations are designed as performance simulations in which we involved several representatives from different public authorities. Findings – The gaming simulations show that interdisciplinary participation can lead to an increased awareness of climate adaptation requirements in particular and a mutual understanding of different logics of action in the context of comprehensive and sustainable urban planning in general. In addition, this paper provides recommendations as to how and under what conditions the benefits of the simulations can be transferred to municipal practice. Originality/value – While integrative and interdisciplinary formats are increasingly being used in the context of informal urban planning, this does not apply to formal urban land-use planning. Participation in formal urban land-use planning procedures is classically linear and multidisciplinary in Germany. Using two simulated interdisciplinary participation formats, this paper tested to what extent the consideration of climate adaptation requirements as a cross-sectoral task can benefit from interdisciplinarity in the context of two formal urban land-use planning procedures.